Analysis of the Effectiveness of User Manual Book in Supporting Application Usage at PT KPI RU 5 - Balikpapan - Ahmad Rifa'i; Ahmad Luthfi (Journal of Software Engineering Ampera, 2025)
In the rapid digitalization era, the User Manual Book (UMB) becomes an essential tool in supporting the use of applications in the industrial environment. This study aims to analyze the effectiveness of the UMB developed during the internship at PT Kilang Pertamina International Refinery Unit V Balikpapan, focusing on enhancing user application usage. The research methods include data collection through user surveys and quantitative and qualitative analysis to measure the UMB's effectiveness. The results indicate that a well-developed UMB significantly improves user efficiency and satisfaction in daily operations. Additionally, the study identifies several areas requiring improvement, including clarity of instructions and information relevance. Recommendations for further improvement of the UMB are presented to support more effective information technology implementation in the future. This study contributes to a better understanding of effective UMB design in the oil and gas industry context.